Optimization of Counseling by Bhabinkamtibmas in Preventing Theft at Majalengka Police in Order to Realize Kamtibmas - Heriawan, Bhakti (Police Studies Review, 2024)
Curanmor phenomenon is still rife, making people uneasy and causing disruption to Kamtibmas. The National Police seeks to maintain Kamtibmas situation through Bhabinkamtibmas counseling which is important in preventing curanmor. A study was aimed at finding about of curanmor to extent which the implementation of Bhabinkamtibmas counseling was related to partnership approach, problem solving efforts and the factors influencing counseling in preventing curanmor to realize kamtibmas at Majalengka District Police. Theories used are Management Theory and Law Enforcement Theory. The concept is the management of Binluh implementation, curanmor, kamtibmas, bhabinkamtibmas and Polmas. This research conducted with qualitative approach, using descriptive analysis methods, data collection by interviewing, observing, and studying documents, also validating data using triangulation of data. The results found that fraud were the most common cases in Majalengka Regional Police. The counseling implementation by Bhabinkamtibmas was not optimal because there still shortages at each stage of the activity and there still deficiencies of Bhabinkamtibmas officers' knowledge about curanmor prevention, the ability to establish partnerships, and communication skills. The inhibiting factors are law enforcement, and cultural, while supporting factors are legal (foundation and formulation), facility, and community. Based on the results of the study, the authors suggest firmness to ensnare the cases of curanmor, prioritize counseling to the lower layers, create a WhatsApp group containing all stakeholders, public lectures on curanmor, mandatory basis for Binmas, rejuvenation of Bhabinkamtibmas, designate Tomas as a 'representative' of Bhabinkamtibmas, increase innovation of creative activities, optimize Sarpras, and hold a Da'i Kamtibmas competition.